2012
DOI: 10.1103/physrevb.85.245407
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced transmission with a graphene-dielectric microstructure at low-terahertz frequencies

Abstract: Here, we report on the transmissivity of electromagnetic waves through a stack of monolayer graphene sheets separated by dielectric slabs at low-terahertz frequencies. It is observed that the multilayer structure possesses band-gap properties and supports a series of bandpass and band-stop regions, similar to the cases of stacked metallic meshes separated by dielectric slabs at microwave/THz frequencies and a metal-dielectric stack at optical frequencies. The transmission resonances in the bandpass region are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 141 publications
(76 citation statements)
references
References 22 publications
6
67
0
1
Order By: Relevance
“…Alternatively, one can use the circuit model described in Refs. 12,13, and 46 to analyze the multilayer stack with the graphene patches modeled as a shunt admittance (Y s = 1/Z s ) across the transmission-line sections.…”
Section: Theoretical Formulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Alternatively, one can use the circuit model described in Refs. 12,13, and 46 to analyze the multilayer stack with the graphene patches modeled as a shunt admittance (Y s = 1/Z s ) across the transmission-line sections.…”
Section: Theoretical Formulationmentioning
confidence: 99%
“…12 that the stacked metallic apertures/mesh-grids at microwave frequencies mimic the transmission properties of a metal-dielectric stack at optical frequencies, and in Ref. 9 it was shown that a graphene sheetdielectric stack at low-terahertz frequencies behaves similar to metallic apertures/mesh-grids. In general, metal patch structures have a capacitive surface reactance, and exhibit a low-frequency passband followed by alternating stop and (generally poorer quality) passbands as frequency increases [see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations